A proposed framework for development of University Enterprise System / Mohd Hairy Mohamaddiah ... [et al.] - Mohamaddiah, Mohd Hairy; Ghazali, Gazairi; Radzi, Ezabarena; Che Kamal, Suraya (2022)
University has developed various type of Enterprise Systems (ES). ES is a package application that consist of business process automation that reflect the common business operations. However, the developed system does not follow any standards or best practices for system development. This resulted the ES has variety of heterogenous architecture. Furthermore, it will complicate the maintenance work in the future for the ES. This paper proposed an empirically derived framework for ES for higher education (university). The framework addresses the standardization of ES development. Based on the study, eight elements are introduced to form the proposed framework.